SOYBEAN ROOT NODES BEHAVIOR IN VARIOUS TREATMENT OF ENRICHED BIOCHAR WITH NPK - Najmi Muhammad Ilmiawan; Sugeng Winarso; Martinus H Pandutama (UNEJ e-Proceeding, 2017)
Biochar is a highly resistant source of carbon to the decomposition process so it can storecarbon in the long term and improve soil characteristics. However, the macro nutrientcontent in biochar is so low that it has not been able to increases soybean plant prductionespecially its dry weight, thus lowering the root nodules. Therefore, biochar needs to beenriched with nutrients, especially NPK, adjusting the requirement of soybean plants bycomparison (8: 5,1: 4) in biochar. The addition of inappropriate nutrients especially nitrogenwill also affect the development of root nodules. Therefore, this study aims to determine (1)the effect of enriched biochar on soil properties, (2) the effect of soil properties on soybeanroot nodules, (3) the best combination of biochar and NPK in improving the development ofroot nodules. This research was conducted using Factorial Randomized Block CompleteDesign (RBCD) consisting of two factors with three replications. The first factor (B): Biocharsource, consisting of four levels and then the second factor (D): Enriched Biochar Dose,consisting of four levels. Based on the correlation result, the root nodules is significantlyinfluenced by soil pH, total N, N uptake, P uptake, and K uptake in acid soil, while measuredphysical and biological characteristic have not significantly influence. Total N and N uptakehave negative correlation so that its enhancement will reduces development of root nodules.The results show that enriched biochar is not significantly influential in increasing total soilN, while significantly reduces soil pH. In soybean crops, enriched biochar significantlyinfluences N, P, and K uptake, vice versa significantly reduces root nodules at doses greaterthan 2.5 ton / ha. The best combination was found in 2.5 ton / ha dose of rice straw biocharand wood biochar for optimize development of root nodules